The acquisition of WH-questions: A simple case in Indonesian children - Fauzi, Iwan (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2012)
In the first stage of language acquisition, children do not give any question word markers to their utterances. The questions without an interrogative word can be thought of yes/noâ nucleus, where the yes/no marker is expressed as rising intonation. The most common wh question forms in children are some version of Whatâs that? and Where Nounphrase (go)? and What Nounphrase doing? This study discusses the typical forms of WH-question construction in Bahasa Indonesia acquired by Indonesian children in the early stage of their language development.